TECHNOLOGICAL ASPECTS OF INFORMATION WARFARE AT THE PRESENT STAGE - Грищук, Руслан Валентинович; Канкін, Іван Олегович; Охрімчук, Володимир Васильович (Ukrainian Information Security Research Journal, 2015)
Known methods and techniques of information warfareat the present stage have been systematized and its maintechnological aspects have been established in the article.It has been shown that the main instrument of informationwarfare today are the social Internet services. It hasbeen proved that the social Internet services, along withthe classical means of information warfare, are used byagents of information struggle for conducting propagandaand counter-propaganda.